2020
DOI: 10.3390/su12229353
|View full text |Cite
|
Sign up to set email alerts
|

Circularity Evaluation of Alternative Concepts During Early Product Design and Development

Abstract: Product design and development are essential for a circular transition. Circularity decisions, such as those concerning the type of material, assembly method, and expected lifespan, made during the early design stages will significantly influence a product’s quality, cost, esthetics, sustainability, and circularity performance over the product lifecycle. However, circularity is not often considered in the early stages of product design and development. This paper presents the development of the concept circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
(69 reference statements)
0
16
0
2
Order By: Relevance
“…Decisions made during the early design stages -such as material selection, assembly method, component accessibility for maintenance -can significantly influence a given product's quality, cost, sustainability, and circularity performance over its lifecycle. Yet, it appears that the circularity performance is often overlooked in the early stages of product design and development [2]. Building up on the momentum around the circular economy concept and the numerous circularity indicator developed in recent years, the present paper helps understand how ad hoc product-centric circularity indicators and their assessment framework can support circular design.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Decisions made during the early design stages -such as material selection, assembly method, component accessibility for maintenance -can significantly influence a given product's quality, cost, sustainability, and circularity performance over its lifecycle. Yet, it appears that the circularity performance is often overlooked in the early stages of product design and development [2]. Building up on the momentum around the circular economy concept and the numerous circularity indicator developed in recent years, the present paper helps understand how ad hoc product-centric circularity indicators and their assessment framework can support circular design.…”
Section: Discussionmentioning
confidence: 98%
“…These four c-indicators were mapped on a two-dimensional chart, with the y-axis indicating the complexity level or time required to use the tool, and the x-axis representing the different steps of the product design process. Kamp Albaek et al [2] have also identified and reviewed four circularity assessment tools that can be used for evaluating product circularity at the concept level or at the early development stage, namely: the CEIP, CET, CPI, and Circular Pathfinder (CP).…”
Section: Literature Survey: Engineering Design Process and Product-level Circularity Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It focuses on improving the environmental performance of a product during its life cycle, without prejudice to other basic criteria such as performance, functionality, aesthetics and quality. The main environmental impacts that are taken into account in ecodesign, include the minimization of material and energy consumption, the selection of less unfavorable materials and the promotion of long-life products (Albaek et al, 2020). Ecodesign focuses exclusively on environmental characteristics and does not consider the social dimensions of sustainability, which cover issues related to the distribution of resources and the related social impacts of a product (Ceschin and Gaziulusoy, 2016).…”
Section: Evolution Of Environmental Design Philosophiesmentioning
confidence: 99%